Pelatihan Pengolahan Sampah dan Aplikasinya pada Budidaya Sayuran Organik bagi Siswa Sekolah Menengah Atas - Wahyu Prihanta; Elly Purwanti; Muizzudin Muizzudin; Feni Tin Faizah (Jurnal Pengabdian UNDIKMA, 2023)
This service activity aims to foster knowledge, attitudes and skills of high school students regarding waste management and its application to organic vegetable cultivation. The community service is carried out through training which consists of the preparation, implementation and evaluation stages. The target partners for this service are SMAN 2 Kota Batu students with a total of 359 students. The evaluation instrument used a questionnaire and was then analyzed descriptively. The results of the service show that this activity has succeeded in growing students' knowledge and skills in processing organic waste into compost and planting organic vegetables from the compost produced. The results of the activity evaluation show that students have been able to carry out waste processing and planting organic vegetables properly and correctly according to the takakura method. The indicator of the success of this service is the increasing of students' skills in processing organic waste and planting organic vegetables. This has been proven by the success of students in processing organic waste at home and the many plants that have been successfully developed from the results of processing organic waste.